Ekspresi Kreativitas Fransisco Jose de Goya y Lucientes - Rizki Kurniawan (JURNAL RUPA, 2017)
As a painter who inspired many of his successor painters, Goya's work not only was trapped by his establishment as a palace painter but also transformed from a portrait painter to a painter with a subversive theme in accordance with the social situation that occured at the time. Goya is always trying to challenge his creativity by trying to bring unusual and controversial themes that are sometimes againts the authority of the palace and the church. With the background of the Goya's creativity process that are so diverse, it is very interesting if we can observe how the creativity process came up with all things that influence it both from the influence of his personal life, environment and socio-political conditions at that time. Keywords: creativity, transformation, challenge, influences.